2003
DOI: 10.1149/1.1621879
|View full text |Cite
|
Sign up to set email alerts
|

Post-Plasma-Etch Residue Removal Using CO[sub 2]-Based Fluids

Abstract: A high pressure CO 2 -based post-etch-residue removal method is described. Tetramethylammonium hydroxide ͑TMAH͒ mixtures containing methanol and water were used as cosolvents with CO 2 . The effect of process parameters such as temperature, time, and cosolvent composition on the residue removal was investigated. X-ray photoelectron spectroscopy and scanning electron microscopy were used to characterize the samples. A 12% w/w of a 4:1 volumetric mixture of 25% TMAH in methanol and deionized water in CO 2 at 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…4, the stripping efficiency was found to be dependent on the temperature at the constant pressure (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The stripping rate increased with the elevated temperature below 60°C, while the reverse results were obtained at 70°C and 80°C.…”
Section: Dependence Of the Removal Rate On The Temperature And Pressurementioning
confidence: 94%
See 2 more Smart Citations
“…4, the stripping efficiency was found to be dependent on the temperature at the constant pressure (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The stripping rate increased with the elevated temperature below 60°C, while the reverse results were obtained at 70°C and 80°C.…”
Section: Dependence Of the Removal Rate On The Temperature And Pressurementioning
confidence: 94%
“…However, scCO 2 is not a good solvent for polar species or polymers like photoresists because of the small cohesive energy and zero dipole moment. Previous studies have shown that the addition of co-solvents and/or surfactants into scCO 2 can enhance solvent strength of scCO 2 [8,17,18]. Hess [18] investigated the effect of scCO 2 /tetramethylammonium hydroxide (TMAH) mixtures containing methanol and water on the removal efficiency of post-plasma-etch residues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These residues contain carbonaceous polymeric mater from the photoresist and silica-based materials from the MSQ containing Si, C, and O with small amount of copper from the metal layer and fluorine from the etch gas [22][23][24][25][26] . The residues could have disadvantages in achieving long-term stability in electrical properties, and must be removed.…”
Section: Cleaning Low-kmentioning
confidence: 99%
“…Tseng et al (2005) have used supercritical CO2 with special co-solvents to clean residue after plasma O2 (6) . Myneni and Hess (2003) used tetramethyl ammonium hydroxide (TMAH) mixtures containing methanol and water as co-solvents with supercritical CO2 (7) . They reported that a 12 %w/w of a 4:1 volumetric mixture of 25 % TMAH in methanol and deionized water in CO2 at 20.7 MPa and 70 °C effectively removed the residue.…”
Section: Introductionmentioning
confidence: 99%